2022
DOI: 10.1037/pag0000657
|View full text |Cite
|
Sign up to set email alerts
|

Age declines in numeracy: An analysis of longitudinal data.

Abstract: Numeracy, the ability to understand and use basic probability and numerical concepts, is associated with diverse positive outcomes across the lifespan. Prior cross-sectional research on numeracy has generally found a negative association with age, but positive correlations with male gender, education attainment, and measures of fluid and crystallized intelligence have been more robust. Age effects on cognitive functioning are well established, but little is known about longitudinal trends of numeracy into olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…These correlations may also reflect age-related changes: an 11-y US-wide longitudinal study found age-related declines in numeracy starting around age 60 y. 12 Indeed, theories of cognitive aging 13 suggest that age-related declines in fluid cognitive abilities may hinder numerical operations. 14,15 Low numeracy is also more common among adults with lower education, according to cross-sectional studies in high-income and upper-middle income countries.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These correlations may also reflect age-related changes: an 11-y US-wide longitudinal study found age-related declines in numeracy starting around age 60 y. 12 Indeed, theories of cognitive aging 13 suggest that age-related declines in fluid cognitive abilities may hinder numerical operations. 14,15 Low numeracy is also more common among adults with lower education, according to cross-sectional studies in high-income and upper-middle income countries.…”
mentioning
confidence: 99%
“…These correlations may also reflect age-related changes: an 11-y US-wide longitudinal study found age-related declines in numeracy starting around age 60 y. 12 Indeed, theories of cognitive aging 13 suggest that age-related declines in fluid cognitive abilities may hinder numerical operations. 14 , 15 …”
mentioning
confidence: 99%
See 1 more Smart Citation